Determinants of Compliance With Iron and Folate Supplementation Among Pregnant Women in West Iran: A Population Based Cross-Sectional Study - Soraya Siabani; Sina Siabani; Hossien Siabani; Marjan Moeini Arya; Fateme Rezaei; Maryam Babakhani (Tehran University of Medical Sciences, 2019)
Objective: To assess the compliance with iron and folate supplementation, and the possibly causally associated factors, among pregnant women in western Iran. Materials and methods: A cross-sectional study of 433 pregnant women, selected randomly amongst those (n = 8,500) attending 40 primary health care centers (PHCCs) in west Iran in 2017. A validated questionnaire was used to gather data, including demographic characteristics, the compliance with iron/folate supplementation and reasons for non-compliance. Results: The participants' mean age and the duration of their pregnancies when commencing supplementation were (27.86 ± 5.54y [µ ± SD]) and (23.29 ± 9.86w), respectively. The compliance was 71.6% / 28% for iron, and 81.5% / 40% for folate. The commonest causes of poor compliance were forgetfulness and side-effects. Educational status, age, and history of anemia were significantly positively associated with folate compliance. The compliance with iron was associated only with the level of education. Conclusion: Although the compliance with iron and folate was relatively high, most women had not started taking the supplements regularly or at the correct time, usually due to forgetting and/or experiencing adverse side-effects.